A study on evaluation of the role of fine-needle aspiration cytology in the etiology of lymphadenopathy in the rural population attending tertiary care hospital - Dr. C. Sitalata; Dr. K. Kalyan (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Lymph nodes are a site for organized collections of lymphoreticular tissue and are pink-gray bean-shaped encapsulated organs. Lymph nodes are among the commonly aspirated organs for diagnostic purposes. Lymphadenopathy is of great clinical significance as underlying diseases may range from a treatable infectious etiology to malignant neoplasms Fine needle aspiration cytology (FNAC) is a reliable as well as an inexpensive method used to diagnose lymphadenopathy of various sites.Aims: To evaluate the usefulness of FNAC as a diagnostic tool in the etiological causes of lymphadenopathy and to study the cytomorphological features associated with various lymphadenopathies.Materials and Methods: The present prospective study was carried out in the Department of Pathology at Maharajah's Institute of Medical Sciences, Vizianagaram, a Tertiary Care Centre. A total of 210 patients of all age groups underwent FNAC of enlarged lymph nodes during this study period.Results: FNAC diagnosis was found to be as follows: tubercular lymphadenitis in 98 cases (46.67%) followed by reactive hyperplasia in 35 cases (16.67%), metastatic carcinoma 29 (13.8%), granulomatous lymphadenitis 27 (12.85%), non-specific lymphadenitis 8 (3.8%), acute suppurative lymphadenitis 7 (3.33%) and lymphoma 4 (1.8).Conclusion: FNAC of lymph nodes is an excellent first-line investigation to determine the nature of the lesion. It is quick, safe, minimally invasive, and reliable and is readily accepted by the patient.